Comparison of the Effect of Two Oral Hygiene Education Approaches on the Gingival Health and Dental Plaque of Boarding School Students in Fariman, Iran - Fatemeh Khorakian; Taraneh Movahhed; Zahra Mohammadzadeh (Mashhad University of Medical Sciences, 2019)
Introduction: The school-based oral health programs are an opportunity to inspire positive attitudes and proper oral health behavior in students. The purpose of this study was to compare the effects of two oral health education methods on the oral health of boarding high school students in Fariman, Iran. Methods: In this interventional study, 345 students were randomly divided into three groups, namely self-led (control), teacher-led (instructed by teachers), and peer-led (instructed by students). All students were subjected to Simplified Oral Hygiene Index (OHI-S), Gingival Index (GI), Plaque Index (PI) measurements before and three months after the intervention. The data were analyzed using the paired t-test, the Kruskal-Wallis, and the Chi-square tests. The P-value less than 0.05 was considered to be significant. Results: The results of the study showed a significant decrease regarding the scores of all three indices (P